2015
DOI: 10.1007/s13312-015-0645-7
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life in Indian children with cystic fibrosis

Abstract: Hindi versions of Cystic Fibrosis Questionnaire- Revised: Child, Adolescent and Parents instruments will act as an important step towards data on Health Related Quality of Life of Indian patients with cystic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Interestingly, in our study, young participants scored rather low in the latter (66.67), while the oldest group had the second highest median (83.34) in that domain, which was similar to older patients in the Borawska-Kowalczyk and Sands study [ 23 ]. High scores in the aspects of digestion were repeated in other studies, suggesting that although there are aspects of CF that may cause digestive problems, patients do not find this aspect of their lives to be as negatively influenced by the disease as other aspects [ 24 , 29 , 32 ]. There were almost no differences between age groups and the assessment of their social functioning (61.90 vs. 61.91 vs. 63.89), which shows that all CF patients suffer in that part of their life regardless of their age.…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, in our study, young participants scored rather low in the latter (66.67), while the oldest group had the second highest median (83.34) in that domain, which was similar to older patients in the Borawska-Kowalczyk and Sands study [ 23 ]. High scores in the aspects of digestion were repeated in other studies, suggesting that although there are aspects of CF that may cause digestive problems, patients do not find this aspect of their lives to be as negatively influenced by the disease as other aspects [ 24 , 29 , 32 ]. There were almost no differences between age groups and the assessment of their social functioning (61.90 vs. 61.91 vs. 63.89), which shows that all CF patients suffer in that part of their life regardless of their age.…”
Section: Discussionmentioning
confidence: 90%
“…While some studies found a high level of agreement in parent-child reports, 20 21 others found that parents were better able to report HRQoL in observable domains, such as physical symptoms. [22][23][24][25] Two studies 26 27 noted that parent-child agreement was better for younger children than older.…”
Section: Mode and Methods Of Administrationmentioning
confidence: 99%
“…80 For paediatric populations, the most common method of administration was self-reporting, using instruments specially designed for use in children. Proxy reporting was uncommon and studies investigating the consistency of parent and child results found that it was better for observable symptoms [22][23][24][25] and younger children. 26 27 Edwards et al 26 hypothesised this finding was because parents are more involved in care for younger children and therefore have a better understanding of their HRQoL.…”
Section: Patient and Public Involvementmentioning
confidence: 99%
“…The participants who had both the adherence rate and the technique score 80% were considered to have good adherence with the correct technique. The secondary outcome measures were change in spirometry parameters, improvement in ease of sputum expectoration as assessed on a 10 cm visual analogue scale (as reported by participants), number of exacerbations, Shwachman-Kulczycki (SK) score, quality of life as assessed using the revised CF-QOL score (Hindi version) (12,13) from baseline to the end of The estimated sample size was 92 for an expected increase of 30% in adherence with the correct technique with 80% power and 5% alpha error, considering 10% lost to follow. We performed intention to treat analysis using standard statistical tests.…”
Section: Airway Clearance Therapy (Act) Is Integral To Management Of ...mentioning
confidence: 99%